THE PORTRAIT OF RURAL TOURISM MODEL IN THE BAHA TOURISM VILLAGE OF BADUNG DISTRICT - Monica Fitria Hartiningsih; I Made Adhika; Komang Trisna Pratiwi Arcana (Institut Pariwisata dan Bisnis Internasional, 2016)
Baha Village designated as tourism village since 1994. However, until now relatively undeveloped as expected. The purpose of this research to determine of tourism existing and the portrait of rural tourism model that took place in Baha Tourism Village. This research used descriptive qualitative method. The informant determined by purposive and utilize qualitative and quantitative data where its sourced from primary data also secondary data. Datas obtained by observation, interviews, and documentation. The research of result was found tourism existing ini Baha Tourism Village in the form of a panoramic expanse of rice fields and visiting to a Balinese traditional house, supported with the adequate accessibility and facilities such as public toilets, wantilan, clean water, electricity and communication networks. Institutional is not yet operational. Baha Tourism Village life cycle stage with the involvement of public attitudes tend to be quiet(Withdrawal). Referring to the existing portrait of rural tourism model at the Baha Tourism Village is a rural tourism model of halffull-passive interaction who initiated by the government and its managed by the individual societies. It can be concluded, Baha Tourism Village has not been categorized as a ideal tourism village.